Task relevancy and demand modulate double-training enabled transfer of perceptual learning - Wang, Rui (2011)
Location-specific perceptual learning can be rendered transferrable to a new location with double training, in which feature training (e.g., contrast) is accompanied by additional location training at the new location even with an irrelevant task (e.g. orientation). Here we investigated the impact of relevancy (to feature training) and demand of location training tasks on double training enabled learning transfer. We found that location training with an irrelevant task (Gabor vs. letter judgment, or contrast discrimination) limited transfer of Vernier learning to the trained orientation only. However, performing a relevant suprathreshold orthogonal Vernier task prompted additional transfer to an untrained orthogonal orientation. In addition, the amount of learning transfer may depend on the demand of location training as well as the double training procedure. These results characterize how double training potentiates the functional connections between a learned high-level decision unit and visual inputs from an untrained location to enable transfer of learning across retinal locations.